Refractory vasospasm of the left anterior descending artery causing hemodynamic instability after percutaneous coronary intervention - Magarkar, Vilas; Borgaonkar, Devendra; Lathi, Pravir (International Journal of Research in Medical Sciences, 2020)
Refractory coronary vasospastic angina is prone to fatal outcomes. Therefore, it is crucial that the most suitable treatment strategy be promptly elected so as to avert further cardiac complications. Here, authors present the clinical course of profound refractory coronary vasospastic angina in a 50-year-old man. Authors elected to manage the patient through stent implantation. Despite, a complication of perforation followed by refractory coronary vasospasm, authors elected to implant a second stent to relieve the patient from all symptoms.